2018
DOI: 10.1103/physrevb.97.085110
|View full text |Cite
|
Sign up to set email alerts
|

Topological dynamics of gyroscopic and Floquet lattices from Newton's laws

Abstract: Despite intense interest in realizing topological phases across a variety of electronic, photonic and mechanical platforms, the detailed microscopic origin of topological behavior often remains elusive. To bridge this conceptual gap, we show how hallmarks of topological modes -boundary localization and chirality -emerge from Newton's laws in mechanical topological systems. We first construct a gyroscopic lattice with analytically solvable edge modes, and show how the Lorentz and spring restoring forces conspir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 129 publications
0
20
0
Order By: Relevance
“…In particular, the applications extend to bosonic band systems such as photonic crystals, 101,102 phonon bands, 103,104 and linear circuit lattices. [66][67][68] Finally, we remark on our definition of a BR -as unitarily equivalent to locally-symmetric Wannier functions. A priori, this definition is not obviously equivalent to the conventional definition [49][50][51][52] of BRs as induced representations of space groups; this equivalence is proven in App.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…In particular, the applications extend to bosonic band systems such as photonic crystals, 101,102 phonon bands, 103,104 and linear circuit lattices. [66][67][68] Finally, we remark on our definition of a BR -as unitarily equivalent to locally-symmetric Wannier functions. A priori, this definition is not obviously equivalent to the conventional definition [49][50][51][52] of BRs as induced representations of space groups; this equivalence is proven in App.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…This type of metamaterial can be utilized to force waves to propagate along a line, whose direction is defined by the geometry of the medium (Carta et al, 2017). Gyroscopic spinners can also be employed to design topological insulators, where waves travel in one direction and are immune to backscattering (Nash et al, 2015;SĂĽsstrunk and Huber, 2015;Wang et al, 2015;Garau et al, 2018;Lee et al, 2018;Mitchell et al, 2018;Carta et al, 2019;Garau et al, 2019;Carta et al, 2020). Furthermore, systems with gyroscopic spinners can be used to design coatings to hide the presence of objects in a continuous or discrete medium (Brun et al, 2012;Garau et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The first model of a gyroscopic elastic lattice in which each nodal mass is connected to a gyroscopic spinner was proposed by Brun et al (2012). The gyroscopic effect can be employed to tune the frequency at which dynamic anisotropy is observed, as shown in the work of Carta et al (2014), to create extremely localised waveforms as demonstrated by Carta et al (2017), to force waves to propagate along a preferential direction illustrated in the works of Nash et al (2015), SĂĽsstrunk & Huber (2015), Wang et al (2015), Garau et al (2018), Mitchell et al (2018), Lee et al (2018), Carta et al (2019a, Garau et al (2019), Carta et al (2020) and to design cloaking devices to hide the presence of an object in continuous and discrete elastic systems. Concerning the latter, see the studies conducted by Brun et al (2012) and Garau et al (2019).…”
Section: Introductionmentioning
confidence: 99%
“…1(b) is linked to the non-reciprocity of the system due to the gyroscopic effect, which is formally demonstrated in the present paper. The idea of connecting gyroscopic spinners to a discrete system in order to generate unidirectional edge or interfacial waves has been proposed by Nash et al (2015), Wang et al (2015), Garau et al (2018), Mitchell et al (2018), Lee et al (2018) and Garau et al (2019) for hexagonal and kagome configurations. In the present paper, the mass points are arranged in a triangular lattice pattern and the attention is focused on Rayleigh surface waves.…”
Section: Introductionmentioning
confidence: 99%